Mobile Learning Application on Two-Dimensional Figure Material for Children with Intellectual Disabilities - Pausi, Ahmad; Rayhan Noerfikri, Mohamad; Tullah, Rahmat; Ferawati, Ferawati (Sinkron : jurnal dan penelitian teknik informatika, 2025)
Mobile learning apps are widely acknowledged for their effectiveness in enhancing learning results. This study aims to develop and validate an mobile learning app for computer two dimensional figure. Using the userfriendly App figma platform known for visual programming, it integrates interactive modules and multimedia for diverse learning styles. The study adopted a Research and Development approach following the ADDIE model (analysis, design, development, implementation, and evaluation). The research was conducted at SKh YKDW 02 Tangerang and involved 6 students. The outcomes pertaining to validation experts percentage scores are as follows: The aspect of media and design received a score percentage of 91,25%, affirming its very valid. Students responses the average percentage for the four assessment aspects clarity of material, motivation, interest, and easy of use navigation reached 91,10%, placing it in the very good category. The development of this mobile learning application for two dimensional figure material for children with intellectual disabilities material demonstrates significant potential as an innovative educational tool.